Factors Associated with Formula Feeding among Late Preterm Neonates - Fishel Bartal, Michal; Chen, Han-Yang; Blackwell, Sean C.; Chauhan, Suneet P.; Sibai, Baha M. (American Journal of Perinatology, 2020)
Objective Late preterm births (delivery at 34–36 weeks) account for nearly three quarters of the preterm births and among them there is a knowledge gap about an important aspect of infant care: breast versus formula feeding. The aim of this study was to assess factors associated with formula feeding in late preterm neonates.Study Design Secondary analysis of a multicenter randomized trial of antenatal corticosteroids for women at risk for late preterm birth. All women with a singleton pregnancy who delivered at 340/7 to 366/7 weeks were included. Women with no information on neonatal feeding or known fetal anomalies were excluded. The outcome evaluated was the type of neonatal feeding during hospital stay. Maternal and neonatal characteristics were compared among women who initiated breast versus formula feeding. Adjusted relative risks (aRRs) for formula feeding with 95% confidence intervals (CIs) were calculated.Results Of the 2,831 women in the parent trial, 2,329 (82%) women met inclusion criteria and among them, 696 (30%) were formula feeding. After multivariable regression, the following characteristics were associated with an increased risk of formula feeding: maternal age < 20 years (aRR: 1.47, 95% CI: 1.20–1.80) or ≥35 years (aRR: 1.19, 95% CI: 1.02–1.40), never married status (aRR: 1.39, 95% CI: 1.20–1.60), government-assisted insurance (aRR: 1.41, 95% CI: 1.16–1.70), chronic hypertension (aRR: 1.19, 95% CI: 1.01–1.40), smoking (aRR: 1.51, 95% CI: 1.31–1.74), cesarean delivery (aRR: 1.16, 95% CI: 1.03–1.32), and admission to neonatal intensive care unit (aRR: 1.31, 95% CI: 1.16–1.48). Hispanic ethnicity (aRR: 0.78, 95% CI: 0.64–0.94), education >12 years (aRR: 0.81, 95% CI 0.69–0.96), and nulliparity (aRR 0.71, 95% CI: 0.62–0.82) were associated with a reduced risk for formula feeding.Conclusion In this geographically diverse cohort of high-risk deliveries, 3 out 10 late preterm newborns were formula fed. Smoking cessation was a modifiable risk factor that may diminish the rate of formula feeding among late preterm births.Key Points
Keywords: late preterm birth; formula feeding; breastfeeding